Antecedents of satisfaction and loyalty in different spectator tribes in a football context. Issue 2 (22nd July 2021) - Lamberti, Giuseppe; Rialp, Josep; Simon, Alexandra
Abstract : Purpose: Extending existing research in a football context, this study explores how image and service quality influence spectator tribe satisfaction and loyalty and variations in behaviors depending on age, gender and emotional involvement. Design/methodology/approach: Spectators aged 18 years and older who attended Barcelona Football Club home La Liga matches were sampled. Partial least squares structural equation modeling (PLS-SEM) was used to analyze the model, and hybrid multigroup PLS-SEM was used to explore observed heterogeneity. Findings: Image and service quality both influence spectator satisfaction and loyalty. Satisfaction and loyalty are associated differently with three tribes: a nonpassionate tribe characterized by low emotional involvement and younger and older passionate tribes composed of emotionally involved spectators aged <30 and >30 years old, respectively. Research limitations/implications: This study's results contribute to strengthening the suitability of PLS-SEM and multigroup in sport management, in particular for analyzing the behavior of specific groups of football spectators. Originality/value: The findings of this study underline image and service quality as crucial to football spectator satisfaction and loyalty, with emotional involvement and age defining different consumer tribes as potential targets for marketing purposes.